The Effect of Organizational Climate on Intention to Stay with Employee Engagement as Intervening Variable - Rizki Dwiputri; Aniek Rumijati; Eka Kadharpa Utama (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to analyze and determine the effect of organizational climate on intention to stay with employee engagement as an intervening variable in Bea Cukai Office Malang. The sampling technique used the purposive sampling technique with a total sample of 50 employees. Data collection techniques in this study used a questionnaire. The data analysis technique used path analysis with the Statistical Product and Service Solutions (SPSS) program. The results of this study indicate that organizational climate has a positive and significant effect on the intention to stay, the organizational climate has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on the intention to stay, the organizational climate has a positive and significant effect of intention to stay with employees. engagement as an intervening variable